Web Based E-Voting System in UUM. - Khaleel, Yousef Kamal Yousef (2007)
The twenty-first century have witnessed several major technological renaissances and many technological achievements as well, which led to a competition among many countries to adapt this trend. Malaysia had improved the infrastructure needed in the information and communication technology area, in order to provide the universities with the new technologies. Therefore the use of the technology becomes available inside the universities which make the idea of electronic voting achievable. To develop e-voting web based system, the study will use the methodology for this study is based on the general methodology in research design, because it is have the logical phases that used to develop a prototype for e-voting web based system to make the election process in student council more efficient and accurate and helping to solve the problems or the difficulties in the traditional voting system (ballot box). Finally, the system is tested and the result confirms that the proposed system is capable to record a successful completion of elections.